Model of Heterogeneous Material Dissolution in Simulated Biological Fluid; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Knyazeva A. G. Anna Georgievna (2015, 2015)
Title screen